2009
DOI: 10.1007/s12011-009-8351-8
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Chromium Histidinate on Mineral Status of Serum and Tissue in Fat-Fed and Streptozotocin-Treated Type II Diabetic Rats

Abstract: The present study was conducted to investigate the effects of chromium histidinate (CrHis) against experimentally induced type II diabetes and on chromium (Cr), zinc (Zn), selenium (Se), manganese (Mn), iron (Fe), and copper (Cu) in serum, liver, and kidney of diabetic rats. The male Wistar rats (n = 60, 8 weeks old) were divided into four groups. Group I received a standard diet (12% of calories as fat); group II were fed standard diet and received CrHis (110 mcg CrHis/kg body weight per day); group III recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
48
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 30 publications
4
48
0
Order By: Relevance
“…In accordance with the findings of the present study, Dogukan et al (2009) found that concentrations of Zn in liver and kidney of the diabetic rats were significantly lower than in the control rats. In contrast, higher Fe and Cu levels were found in tissues from diabetic versus the non-diabetic rats.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the findings of the present study, Dogukan et al (2009) found that concentrations of Zn in liver and kidney of the diabetic rats were significantly lower than in the control rats. In contrast, higher Fe and Cu levels were found in tissues from diabetic versus the non-diabetic rats.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, we also demonstrated that this beneficial effect of SC could also be due to attenuation of oxidative stress, TNF-α, β-cell damage and dysfunction. Our findings was in consonance with the previous studies demonstrating that animals fed with HFD and injected a low dose STZ display many characteristics of IR including significant obesity, fasting hyperglycemia, hyperinsulinemia, β-cell dysfunction, hyperlipidemia, and increased serum TNF-α levels (20,21). Furthermore, we also observed increased lipid peroxidation, decreased antioxidant enzyme activity and deleterious changes in pancreatic β-cells in HFD-STZtreated rats.…”
Section: Discussionsupporting
confidence: 93%
“…STZ-induced elevation of iron storage was also observed in the proximal tubular lysosomes (27), myocardium (28), and artery (29), while studies of Silva et al (30) and Saravanan et al (31) showed that serum iron was increased in STZ rats. Additionally, Dogukan et al (32) reported that STZ injection following HFD induction markedly increased the hepatic and serum iron levels. Our results demonstrated that insulin therapy effectively released HIO, manifested by the recovery of liver iron content and serum ferritin and the improvement tendency of serum sTfR, and lowered serum iron to normal level in STZ-induced both type 1 and type 2 diabetic rats.…”
Section: Discussionmentioning
confidence: 99%